Case Report: Severe Edema and Marked Weight Gain Induced by Marginal Thiamine Deficiency in a Patient With Alcohol Dependency and Type 2 Diabetes Mellitus - Tanaka, Hitomi; Anno, Takatoshi; Takenouchi, Haruka; Iwamoto, Hideyuki; Kaneto, Hideaki; Okimoto, Niro; Tomoda, Koichi (Frontiers in Nutrition, 2021)
Background: Patients with alcohol use disorder (AUD) may develop peripheral edema due to alcohol-related liver, renal or heart disease. Thiamine deficiency is reported to occur in AUD and type 2 diabetes mellitus (T2DM). Thiamine deficiency may also cause peripheral edema. Thiamine is essential for optimal glucose metabolism through its role as an essential co-factor for key enzymes in intermediary metabolism. Since glucose metabolism worsens under diabetic conditions, it seems that relative shortage of thiamine may occur more easily in patients with diabetes mellitus. Case presentation: A 59-year-old Japanese man was admitted to hospital with severe peripheral edema. His background history included alcohol liver disease (ALD), chronic renal failure (CRF) and T2DM. His BMI at admission was 37.7 kg/m2 and this represented 30 kg increase in body weight over 2 months. Laboratory investigations showed anemia, liver and renal injury, hyperglycemia and marginal hypothyroidism. Plasma thiamine diphosphate concentration was 20 ng/mL (reference range: 24-66 ng/mL). Diet therapy of 1600 kcal/day and intravenous fursultiamine hydrochloride therapy (50 mg/once a day, 7 days) was commenced in combination with intravenous diuretics. After 1 week, the plasma thiamine concentration was 853 ng/mL, and the patient’s body weight had reduced by 18 kg. Conclusions: Patients with T2DM and AUD may develop severe peripheral edema in the context of marginal thiamine deficiency. Fursultiamine hydrochloride (50 mg/once a day, 7 days) restored normal plasma thiamine concentrations and may have contributed to rapid resolution of severe peripheral edema in this case. Empirical treatment with thiamine should be considered in patients with severe peripheral edema in the context of AUD and T2DM.